Comparing the magnetic resonant coupling radiofrequency stimulation to the traditional approaches: Ex-vivo tissue voltage measurement and electromagnetic simulation analysis - Yeung, Sai Ho (2015)
Recently, the design concept of magnetic resonant coupling has been adapted to electromagnetic therapy applications such as non-invasive radiofrequency (RF) stimulation. This technique can significantly increase the electric field radiated from the magnetic coil at the stimulation target, and hence enhancing the current flowing through the nerve, thus enabling stimulation. In this paper, the developed magnetic resonant coupling (MRC) stimulation, magnetic stimulation (MS) and transcutaneous electrical nerve stimulation (TENS) are compared. The differences between the MRC RF stimulation and other techniques are presented in terms of the operating mechanism, ex-vivo tissue voltage measurement and electromagnetic simulation analysis. The ev-vivo tissue voltage measurement experiment is performed on the compared devices based on measuring the voltage induced by electromagnetic induction at the tissue. The focusing effect, E field and voltage induced across the tissue, and the attenuation due to the increase of separation between the coil and the target are analyzed. The electromagnetic stimulation will also be performed to obtain the electric field and magnetic field distribution around the biological medium. The electric field intensity is proportional to the induced current and the magnetic field is corresponding to the electromagnetic induction across the biological medium. The comparison between the MRC RF stimulator and the MS and TENS devices revealed that the MRC RF stimulator has several advantages over the others for the applications of inducing current in the biological medium for stimulation purposes.